The organizational configuration concept as a contribution to the performance explanation: the case of the pharmaceutical industry in Portugal - Pinto, J. C.; Curto, J. D. (European Management Journal, 2007)
Framing the Miles and Snow typology with the organizational configuration concept, the main purpose of this paper is to present an empirical evaluation of what configurational theories postulate in terms of organizational performance. However, as it is often assumed that an organization can increase performance by selecting the adjustable hybrid form to its own exogenous environment, the relation between the organization's effectiveness and the hybrid configuration alignment to the respective specific environment type was also analyzed. In short, the main results show that configurational misfit has negative and a statistically significant impact on the organizational performance.